THE INFLUENCE OF PROMOTION MIX AND PROFESSIONALISM ON PURCHASING DECISIONS AND CUSTOMER SATISFACTION THROUGH TRUST MEDIATION AT THE DEL' AMOUR BEAUTY CLINIC IN YOGJAKARTA - ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2026)
The development of Indonesian women's interest in looking beautiful continues to increase along with advances in technology and aesthetic trends. Thus, the beauty clinic industry has grown in many big cities in Indonesia, especially in Yogyakarta. This study aims to determine the effect of promotion mix and professionalism on purchasing decisions and customer satisfaction through trust mediation at the Del' Amour beauty clinic in Yogyakarta. The study used incidental sampling of customers who received treatment at the clinic using a questionnaire according to the Roscoe method of 150 respondents. The results of the study show that the promotion mix has a significant positive direct effect on trust and purchase decisions, as well as professionalism which has a significant positive effect on trust and customer satisfaction. The trust variable is proven to be a mediating/full mediation variable between professionalism towards purchasing decisions and customer satisfaction. And it is not proven that trust is a mediating variable between promotion mix on purchasing decisions and customer satisfaction (only as part mediation).